TIPOLOGI MAJELIS TAKLIM DI KOTA BOGOR TIMUR - Umi Masfiah (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
There are 487 majelis taklim at Bogar City and 102 at East Bogar sub district. These figures represent trend in the Bogarcommunity, especially in East Bogar sub district, to actualize theirreligious life. Popularity of majelis ta/dim phenomenon is not an un-historicprocess; it is a continuous and compound process. Socialimprovements occurred in Bogar City community, especially in EastBogar, because of development processes, have vary religious life,both in activities media and in understanding urgent Islamicconcepts. Three objects referred to observe comprehension andvariety in the community in this research are polygamy, allotment ofinheritance, and hajj. Those objects are related to the popularityof majelis taklim phenomenon, in the village, in the real estatecomplex or even in the governmental institutes. Based on observation of majelis taklim phenomenon atEast Bogar sub district, there are two conclusions, namely:1. There are two factors which cause the popularity of majelistaklimat East Bogar sub district, namely ustadz s orientation andmajelis taklim community s orientation .. Ustadz s orientation isrelated to transfer of knowledge which ustadz has. Each santriwho just come home from Islamic boarding house or just passedfrom Islamic higher education tend to form majelis taklim or becomeustadz of a majelis taklim. Community s orientation is related to noactivities factors, self-actualization, and social interaction althoughmotivation toget better religious understanding is a dominant factor.2. Typology of understanding religious objects related topolygamy.inheritance law, and hajj is divided into 2 (two) aspects:a.In ustadz community, there are two trends1). Understanding polygamy, inheritance law and hajj by rientation to texts as religious reference 2). Understanding polygamy, inheritance law and hajjby Orientation to texts as religious medium. b. Typology of community understanding of religious objectselated to polygamy, inheritance law and hajj is also divided intotwo trends as their ustadz s typology. It is also influenced by statusand economic factors.